The Influence of Motivation Against Employee Turnover in an Organization: Case PT. Energi Mega Persada Tbk - Pradifa, Ismail Aulia; Welly, John (Journal of Business and Management, 2014)
Abstract-Rapidly changing environment requires organizations to respond quickly to these changes in order to remain in the global competition. Organizations often have to change the structure and form of organization in order to respond the environmental changes as well as internal and external pressures. In despite of pressures from internal and external environment, companies must focused on motivating their employees. With the aim of motivating their employees, the company delivers benefit to their employees. Somehow, the benefit from the company not in accordance with employee values and needs. This phenomena trigger the intention to quit from the company or employee turnover. PT. Melati is now one of the biggest National oil and gas companies in Indonesia. Of course this can not be separated from the role of employees is very important to manage and promote the company. In this situation, keep employees in order to stay motivated to work is a must for PT. Melati. There are four major factors according to the theories and exit interview, salary, advancement opportunities (career development), company benefit and job challenge. Four factors are of particular interest to understand and analyze by the writers to prove the corellation with the increase in the employee turnover rate PT. Melati. In the research, the methodology used is the quantitative methods that will give a general view about the influence of motivation with employee turnover. Questionnaire will distribute to the employee and processed by SPSS v.18. Once done with quantitative method by using SPSS program version 1.8, it can be concluded that there are two factors that affect the motivation of employee turnover and two factor motivation that have no effect on employee turnover in the case of organization of PT. Melati. Variable salary and career development are two of the most variable influenced on employee turnover. Two variables are the two main factors that affect employee turnover at PT. Melati. In other words, PT. Melati has a problem with two of these variables.Â Keywords: PT. Melati, Motivation, Employee Turnover